The Objectivity of Accountants' Litigation Support Judgments. - Ponemon, Lawrence A. (The Accounting Review, 1995)
Examines accountants' objectivity when serving as a litigation specialist and expert witness on legal cases. Influence of possible conflicts of interest in litigation support role on professional objectivity; Influence of ethical reasoning and experience on accountants' objectivity.